2015
DOI: 10.5194/bg-12-3789-2015
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of tephra constituents during biogenic silica determination: implications for soil and palaeoecological studies

Abstract: Abstract. Biogenic silica (BSi) is used as a proxy by soil scientists to identify biological effects on the Si cycle and by palaeoecologists to study environmental changes. Alkaline extractions are typically used to measure BSi in both terrestrial and aquatic environments. The dissolution properties of volcanic glass in tephra deposits and their nanocrystalline weathering products are hypothesized to overlap those of BSi; however, data to support this behaviour are lacking. The potential that Si-bearing fracti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…NaOH chemical continuous extraction in parallel with Al showed that clay minerals and other pedogenic Si fractions display initial fast dissolution dynamics, very similar to amorphous silica. This was shown in aquatic samples [30] and in soil samples of different origins [25,28,31]. Other studies using different methods have also hinted that non-biogenic fractions occurring in the soil show similar dynamics to the biogenic Si fractions in alkaline environments [19,21,32].…”
Section: Significance Of Non-bsi Poolsmentioning
confidence: 69%
“…NaOH chemical continuous extraction in parallel with Al showed that clay minerals and other pedogenic Si fractions display initial fast dissolution dynamics, very similar to amorphous silica. This was shown in aquatic samples [30] and in soil samples of different origins [25,28,31]. Other studies using different methods have also hinted that non-biogenic fractions occurring in the soil show similar dynamics to the biogenic Si fractions in alkaline environments [19,21,32].…”
Section: Significance Of Non-bsi Poolsmentioning
confidence: 69%
“…The selected sediment sections were sampled in contiguous 1 cm intervals with a volume of 1 cm 3 and chemically pre-treated with 30% H 2 O 2 overnight in order to remove organic matter. Subsequently, a 7-10% HCl solution was added for a maximum of 1 hour to dissolve carbonates, and a 2M Na 2 CO 3 solution was used for 6-7 hours in a 70-80°C water bath to dissolve biogenic silica (diatoms) instead of more aggressive NaOH (Rose et al, 1996;Davies et al, 2003;Clymans et al, 2015). The remaining material was wet-sieved, and the 20-100 µm grain size fraction was transposed to transparent plastic boxes for microscopic inspection of volcanic glass.…”
Section: Methodsmentioning
confidence: 99%